Comparison of the Effectiveness of Schema-Based Parenting and Mindful Parenting on Sleep Problems, Aggression, and Improvement of Social Interactions in Children with Mild Autism Spectrum Disorder - Bakhtiari Shahri, Sedigheh; Rajaei, Alireza; Pourhydari, Sepideh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of the present study is to compare the effectiveness of schema-based parenting and mindful parenting on sleep problems, aggression, and improvement of social interactions in children with mild autism spectrum disorder.Methods and Materials: The present study is applied in terms of its aim and quasi-experimental in terms of method, using a pretest-posttest design with a control group and a one-month follow-up period. The statistical population includes all children aged 7-12 years with mild autism spectrum disorder who were studying and receiving education in one autism center under the supervision of the Ministry of Education (Tabassum) and five autism centers under the supervision of the Welfare Organization (Ava, Armaghan Noor, Kavosh, Navid-e-Zendegi, and Takapo) in Mashhad. The groupings were conducted through random assignment. Out of these, 40 children (20 boys and 20 girls) and 40 mothers were selected as the research sample using purposive sampling. They were then randomly assigned to three groups: two experimental groups (each with 13 members) and one control group (with 14 members). Data collection was conducted using the Autism Social Skills Profile by Belini and Hopf (2007), the CARS questionnaire by Schopler (1988), the Aggression Questionnaire, and the Children's Sleep Habits Questionnaire by Owens, Spirito, and colleagues (2000). After collecting the questionnaires, the data were analyzed using SPSS-20 software.Findings: The results indicated differences in the effectiveness of schema-based parenting and mindful parenting on aggression in children with mild autism spectrum disorder. Additionally, there were differences in the effectiveness of schema-based parenting and mindful parenting on the improvement of social interactions in children with mild autism spectrum disorder. Furthermore, differences were observed in the effectiveness of schema-based parenting and mindful parenting on sleep problems in children with mild autism spectrum disorder.Conclusion: The study demonstrated that both schema-based and mindful parenting interventions significantly reduce aggression and sleep problems while enhancing social interactions in children with mild autism spectrum disorder. These findings suggest the effectiveness of incorporating these approaches in parenting programs to improve behavioral and emotional outcomes in children.